Correction: Natural bamboo leaves as dielectric layers for flexible capacitive pressure sensors with adjustable sensitivity and a broad detection range. Issue 42 (27th July 2021) - Liu, Zhihao; Liang, Tianlong; Xin, Yue; Huang, Jinhao; Liang, Jionghong; He, Xiang; Zhang, Chi; Yang, Weijia; He, Xin
Abstract : Correction for 'Natural bamboo leaves as dielectric layers for flexible capacitive pressure sensors with adjustable sensitivity and a broad detection range' by Zhihao Liu et al., RSC Adv., 2021, 11, 17291–17300. DOI: ; 10.1039/D1RA03207K .